Insights into symbiotic interactions from metatranscriptome analysis of deep‐sea mussel Gigantidas platifrons under long‐term laboratory maintenance. Issue 2 (17th November 2022) - Sun, Yan; Wang, Minxiao; Chen, Hao; Wang, Hao; Zhong, Zhaoshan; Zhou, Li; Fu, Lulu; Li, Chaolun; Sun, Song
Abstract: Symbioses between invertebrates and chemosynthetic bacteria are of fundamental importance in deep‐sea ecosystems, but the mechanisms that enable their symbiont associations are still largely undescribed, owing to the culturable difficulties of deep‐sea lives. Bathymodiolinae mussels are remarkable in their ability to overcome decompression and can be maintained successfully for an extended period under atmospheric pressure, thus providing a model for investigating the molecular basis of symbiotic interactions. Herein, we conducted metatranscriptome sequencing and gene co‐expression network analysis of Gigantidas platifrons under laboratory maintenance with gradual loss of symbionts. The results revealed that one‐day short‐term maintenance triggered global transcriptional perturbation in symbionts, but little gene expression changes in mussel hosts, which were mainly involved in responses to environmental changes. Long‐term maintenance with depleted symbionts induced a metabolic shift in the mussel host. The most notable changes were the suppression of sterol biosynthesis and the complementary activation of terpenoid backbone synthesis in response to the reduction of bacteria‐derived terpenoid sources. In addition, we detected the upregulation of host proteasomes responsible for amino acid deprivation caused by symbiont depletion. Additionally, a significant correlation between host microtubule motor activity and symbiont abundance was revealed, suggesting the possible function of microtubule‐based intracellular trafficking in the nutritional interaction of symbiosis. Overall, by analyzing the dynamic transcriptomic changes during the loss of symbionts, our study highlights the nutritional importance of symbionts in supplementing terpenoid compounds and essential amino acids and provides insight into the molecular mechanisms and strategies underlying the symbiotic interactions in deep‐sea ecosystems.